Karakteristik Kecepatan Gelombang Geser (Vs) Menggunakan Metode Multichannel Analysis of Surface Wave (MASW) di Bandara Internasional Yogyakarta - Tisar Dewi Pratiwi; Mitranikasih Laia; Rohmawati Metaningrum (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Reliable information on subsurface conditions is essential during the planning and development of airport infrastructure, as variations in soil properties can signiticantly affect foundation stability and construction performance. Shear wave velocity (Vs) is an important geophysical parameter for assessing the mechanical behavior and lithological characteristics of near-surface materials. This study aims to analyze shear wave velocity (Vs) as an indicator of subsurface lithological characteristics at Yogyakarta International Airport using the Multichannel Analysis of Surface Waves (MASW) method. The MASW technique was applied due to its effectiveness as a non-destructive method for obtaining Vs profiles relevant to geotechnical evaluation. The results indicate that at depths of 1–4 m, shear wave velocities range from 220.2 m/s to 315.7 m/s, corresponding to loose sand lithology. At greater depths of 5–15 m, the Vs values increase to between 370 m/s and 390 m/s, indicating more compact sand layers. These findings suggest that the shallow subsurface is dominated by weathered, loose, and soft materials, which are less favorable for supporting heavy infrastructure such as airport runways.